2019
DOI: 10.1021/acsami.9b04255
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Ru@C4N Electrocatalyst for Hydrogen Evolution Reaction in Both Acidic and Alkaline Solutions

Abstract: We report a high-performance Ru@C 4 N electrocatalyst for the hydrogen evolution reaction (HER) in both acidic and alkaline solutions. This catalyst is synthesized by annealing a complex of a covalent organic framework compound coordinated with ruthenium synthesized by a "onepot" solvothermal method. This Ru@C 4 N catalyst shows excellent electrocatalytic activity toward the hydrogen evolution reaction (HER) in both acidic and alkaline solutions with very low overpotentials at 10 mA/cm 2 (6 mV in 0.5 M H 2 SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…As can be seen from Fig. 2 (a), the IR spectra of the starting precursors of HKH and BPTA are distinct from that of C 4 N. The carbonyl group (C = O) at 1637 cm −1 for HKH disappears while the characteristic band at 1612 cm −1 assigned to C = N stretching in pyrazine rings appears, confirming the formation of the C 4 N chemical structure [26] . In the solid -state 13 C NMR spectra, C 4 N exhibited two NMR signals located at 129 and 141 ppm attributed to the C = C carbons of benzene rings and the C = N carbons in pyrazine rings of C 4 N, respectively, and no residual carbonyl signal around 190 ppm of the starting monomer HKH was observed [27] , which further verify the successful generation of the C 4 N structure ( Fig.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…As can be seen from Fig. 2 (a), the IR spectra of the starting precursors of HKH and BPTA are distinct from that of C 4 N. The carbonyl group (C = O) at 1637 cm −1 for HKH disappears while the characteristic band at 1612 cm −1 assigned to C = N stretching in pyrazine rings appears, confirming the formation of the C 4 N chemical structure [26] . In the solid -state 13 C NMR spectra, C 4 N exhibited two NMR signals located at 129 and 141 ppm attributed to the C = C carbons of benzene rings and the C = N carbons in pyrazine rings of C 4 N, respectively, and no residual carbonyl signal around 190 ppm of the starting monomer HKH was observed [27] , which further verify the successful generation of the C 4 N structure ( Fig.…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, C 4 NNSs display similar powder X -ray diffraction (XRD) pattern with the bulk sample featuring a broad diffraction peak at 25.6 ° (Fig. S1) [26] , while the FT -IR spectrum of C 4 NNSs present almost identical signals with respect to the bulk C 4 N ( Fig. 3 (c)).…”
Section: Introductionmentioning
confidence: 77%
“…The corresponding D and G characteristic peaks of carbon materials refer to disordered and defective carbon atoms and graphitized carbon atoms, respectively. 19,20 The peak strength ratio (I D /I G ) before and aer carbonization is 1.0748 and 1.1602 respectively. High temperature carbonization increases the disorder, defect and graphitization of carbon nanotubes, improves the electrochemical active center of carbon nanotubes and the adhesion point and conductivity of ruthenium, which is benecial to the improvement of electrocatalytic hydrogen evolution performance.…”
Section: Resultsmentioning
confidence: 98%
“…For example, the kinetics on Pt in alkaline HER is several orders of magnitude lower than that in acidic solutions, but the activity differences for Ru-based electrocatalysts in acidic and alkaline solutions are marginal. [236][237][238] Zheng et al reported an anomalous fcc Ru catalyst fabricated through reduction and annealing treatment. 239 This catalyst showed 2.5 times higher hydrogen generation rate than that of Pt in 0.1 M KOH.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%